Prevalence and risk factors of allergies in Turkey: Results of a multicentric cross-sectional study in children - Kurt, Emel; Metintas, Selma; Basyigit, Ilknur; Bulut, Ismet; Coskun, Evsen; Dabak, Sennur; Kalyoncu, A. Fuat (Wiley, 2007)
The Prevalence And Risk Factors of Allergies in Turkey (PARFAIT) study was planned to evaluate prevalence and risk factors of asthma and allergic diseases and also to find out which geographical variables and/or climatic conditions play a role determining the prevalence of allergic diseases in Turkish school children. Study was planned as cross-sectional questionnaire-based. About 25,843 questionnaires from 14 centers were appropriate for analysis. Parental history of allergy, having an atopic sibling and other atopic disease in index case was significant risk factors for all allergic diseases. Breast feeding decreased the risk of current asthma (OR: 0.92, CI: 0.86-0.99) and wheezing (OR: 0.93, CI: 0.87-0.99) but not allergic rhinitis and eczema. Respiratory infection in the past was an important risk factor for the occurrence of allergic diseases especially for asthma which was increased 4.53-fold. Children exposed to household smoke were significantly at higher risk of asthma, wheezing, and allergic rhinitis (OR: 1.20, CI: 1.08-1.33; OR: 1.21, CI: 1.09-1.34; and OR: 1.32, CI: 1.21-1.43, respectively). All allergic diseases were increased in those children living in areas which have altitude of below 1000 m and mean yearly atmospheric pressure above 1000 mb. The study has suggested that household and country-specific environmental factors are associated with asthma, wheezing, allergic rhinitis, and eczema risk during childhood in Turkey.
Keywords: allergic diseases; asthma; climate; risk factors; prevalence